Introduction - Lynn A. Higgins (Studies in 20th & 21st Century Literature, 1985)
From an issue of the Magazine Litteraire featuring the work of Fernand Braudel to an article by Hayden White on the "Absurdist moment" in criticism, it is clear that the disciplines of history and literary studies are converging. Historians like White and Dominick La Capra in the United States, and Michel de Certeau and the members of the Annales School in France are investigating the rhetorical modes of their craft and exploring implications of the fact that it is historians themselves who "make history." At the same time, literary scholars, emerging from Structuralism and the New Criticism, are seeking with increasing urgency to understand the historical dimensions of fiction. By bridging the gap between story and history and by opening lines of dialogue between two traditionally separate. even hostile, fields of inquiry, the essays in this issue of Studies in Twentieth Century Literature provide support for the recent assertion that to raise the question of the historical within literary studies is "the most vital stance to take at this particular moment in history..."
Keywords: history; French literature; literary studies; White; American Literature; Dominick La Capra; Michel de Certeau; Annales School; rhetorical mode; historians; literary scholars; Structuralism; New Criticism; fiction